Anti-AMPA GluA3 antibodies in Frontotemporal dementia: a new molecular target - B. Borroni (Nature Portfolio, 2017)
Abstract Frontotemporal Dementia (FTD) is a neurodegenerative disorder mainly characterised by Tau or TDP43 inclusions. A co-autoimmune aetiology has been hypothesised. In this study, we aimed at defining the pathogenetic role of anti-AMPA GluA3 antibodies in FTD. Serum and cerebrospinal fluid (CSF) anti-GluA3 antibody dosage was carried out and the effect of CSF with and without anti-GluA3 antibodies was tested in rat hippocampal neuronal primary cultures and in differentiated neurons from human induced pluripotent stem cells (hiPSCs). TDP43 and Tau expression in hiPSCs exposed to CSF was assayed. Forty-one out of 175 screened FTD sera were positive for the presence of anti-GluA3 antibodies (23.4%). FTD patients with anti-GluA3 antibodies more often presented presenile onset, behavioural variant FTD with bitemporal atrophy. Incubation of rat hippocampal neuronal primary cultures with CSF with anti-GluA3 antibodies led to a decrease of GluA3 subunit synaptic localization of the AMPA receptor (AMPAR) and loss of dendritic spines. These results were confirmed in differentiated neurons from hiPSCs, with a significant reduction of the GluA3 subunit in the postsynaptic fraction along with increased levels of neuronal Tau. In conclusion, autoimmune mechanism might represent a new potentially treatable target in FTD and might open new lights in the disease underpinnings.